Morphometric description of uterus wall of the irradiated animals posterity - Ulyanov V.O.; Napkhanyuk V.K. (Морфологія, 2008)
The morphometric parameters of uterus wall in postnatal ontogenesis of first generation offsprings after -ray exposure of male and female rats before coupling were investigated. The animals were exposured by total fractionating -irradiation in a dose 1,0 Gy. The animals were allowed to couple after completion of irradiation. The thickness of myometrium and endometrium of first generation offsprings were measured on 14th, 30th and 90th day of postnatal ontogenesis. The formation of uterus wall layers in first generation offsprings of exposured animals was impaired in postnatal ontogenesis. We observed structural abnormalities and changes of the normal ratio of thickness of uterus wall layers in different age periods.